The effects of charring on sunflower (Helianthus annuus L) achenes and kernels: Taphonomic and behavioral implications - John P. Hart (PLoS ONE, 2025)
Sunflower (Helianthus annuus L) is one of several seed-bearing annual plants that were domesticated in eastern North America 5000–3800 years ago. When found in the archaeological record the plant’s fruits (achenes) are generally charred. Charring causes changes in the lengths and widths of achenes and their enclosed kernels. Correction factors for these changes derived from controlled heating experiments have been proposed to estimate the original size of charred achenes. The resulting corrected sizes are used to distinguish achenes from domesticated and wild sunflowers. The current study aimed to assess the accuracy of these correction factors and explore morphological differences in hulled and unhulled kernels after heating in 20°C increments from 200 to 420°C. The results indicate the proposed correction factors are inaccurate, potentially leading to type 1 and type 2 errors in assessing domestication status of achenes; the use of correction factors to identify domesticated sunflower achenes is not warranted. Rather, size comparisons of charred archaeological to charred wild contemporary sunflower achenes reported in a previous experiment are less likely to result in assignment errors. Results also indicate it is possible to distinguish between kernels that were hulled before charring from those that were not hulled based on length:width ratios and the presence of longitudinal ridges on unhulled kernels.